Imitation and the developing social brain: infants’ somatotopic EEG patterns for acts of self and other - Peter J. Marshall (Universidad de San Buenaventura, 2013)
A leading question in developmental social-cognitive neuroscience concerns the nature and function of neural links between action perception and production in early human development. Here we document a somatotopic pattern of activity of the sensorimotor EEG mu rhythm in 14-month-old infants. EEG was recorded during interactive trials in which infants activated a novel object using their own hands or feet (“execution” trials) and watched an experimenter use her hands or feet to achieve the same goal (“observation” trials). At central electrodes overlying sensorimotor hand areas (C3/C4), mu rhythm power was reduced (indicating greater cortical activation) during infants’ execution of hand acts compared to foot acts. For the central electrode overlying the sensorimotor foot area (Cz), mu power was reduced during the execution of foot versus hand acts. Strikingly similar somatotopic patterns were found in both the action execution and observation conditions. We hypothesize that these somatotopic patterns index an intercorporeal mapping of corresponding body parts between self and other. We further propose that infants’ ability to identify self-other equivalences at the level of body parts underlies infant imitation and is an ontogenetic building block for the feelings of intersubjectivity we experience when socially engaged with other people.